Antibacterial activity of the marine sponge Ircinia Campana collected at Punta Uva Limón against Staphylococcus Aureus - Rojas Brenes, Rafael (2012)
The sponges are simple multicellularorganisms; they inhabit in marine environments from the polar seas to the tropical waterswhere they are more abundant. These species are exposed to large populations of microbes, reason that explains their complex morphological and cellular defense mechanism, which are used by these organisms to fight against pathogens. The purpose of this study was to evaluate the antibacterial activity of the marine sponge Ircinia campana, whichinhabits in the south of the Caribbean coast of Costa Rica against  Sthapylococcus aureus gram-positive bacteria. Sampleswere collected in Punta Uva in Limónduring July of 2007. The active compounds were obtainedby extraction with acetone (crude extract); and subsequently, chromatographic extracts were obtained using fractions 1:4 hexane: ethyl acetate. The antibacterial activities of the different fractions, including the  crude extract were tested.Our results suggest a zone of inhibition of 14.60 ±0.25 mm for the crude extract and18.70±0.25mm for the most active fraction separated by chromatography. The metabolite responsible for the antibacterial activity was isolated by High Performance Liquid Chromatography (HPLC)and preliminarily characterized through ultraviolet (UV) and infrared (IR) spectroscopy.